The Impact of The Fatherless on Gen Z in The Era of Society 5.0 - Hana Fitriani; Risna Rogamelia , (Proceedings Of International Conference On Islamic Counseling Studies (ICONICS), 2025)
Parents and family are the main foundation for the growth and development of children. The parenting pattern given by parents will have an impact on the behavior and moral intelligence of children. If in the care of children there is a dominant figure, then maximum child growth will not be obtained. The father's duty as the head of the household is not only to earn a living, but the father is also tasked with playing a role in the pattern of parenting for children. Especially when the child has entered adolescence, the father figure as a friend and father as a parent is needed so that unwanted things do not happen to the child. Fatherless occurs due to lack of interaction between father and son and lack of awareness of his duties as a father as well as inappropriate parenting factors. For this reason, good parenting and cooperation between father and mother is needed to make preventive efforts so that children do not experience fatherlessness and that undesirable things do not happen.